Community of Inquiry for Students’ Autonomy in English Language Learning: A Case of Philippines High School - Rachman, Alqy Novia; Maghfiroh, Ana; Mustikawati, Diyah Atiek; Indriastuti, Niken Reti (IJELTAL (Indonesian Journal of English Language Teaching and Applied Linguistics), 2021)
There were many researchers bring out the topic of the community of inquiry (CoI) in education but there were still few teachers who were aware of the importance of CoI and how to implement CoI into learning. This study was, then, aimed at finding out (1) how the community of inquiry was explicitly applied to English language learning, as well as (2) the impact of the community of inquiry to promote students’ autonomous learning. This research was a case study. The researcher used observation and interview as the research instrument. The subjects were the seventh and eighth-grade students of Pangasinan State University (PSU) Integrated High School, Philippines. The sample has consisted of 101 participants from three classes: 7th-grade Malakas and Maganda, and 8th-grade Matapat. The finding showed that CoI had been implemented during the English language teaching and learning process. Group activity or collaborative task was mostly used to engage students to learn and work in a community. In language acquisition, CoI was supposed to provide students with not only cognitive intelligence but also much-needed social intelligence. Therefore, the CoI approach has been considered to be effective in language teaching activities for secondary education students to enhance students’ autonomous learning.